Foresight and trade-offs analysis to identify innovative solutions for agricultural sustainability in Pakistan - Hafeez, Mohsin; Davies, Stephen; Akram, Iqra; Ali, Muhammad Tahir; Ringler, Claudia (International Water Management Institute, 2025)
A team of researchers from IWMI and IFPRI are exploring hydro-economic modeling and trade-offs in the agricultural sector to achieve water, food security and sustainability in regions facing growing resource constraints.